Leader’s Motivation Language – A Study on Internal Communication at National Library of Indonesia - Ade Farida; Leila Mona Ganiem (Ikatan Sarjana Komunikasi Indonesia, 2017)
This article presents the result of the study on understanding the Leader Motivating Language in daily internal communication in the work environment of Indonesian National Library. It uses MLT as a model and framework. The methodology is conducting deep interviews of senior staffs in the organization that have significant roles in the organization strategic vision goals. Result shows that MLT’s used by the leader in birocratic organization confine the interaction using MLT of leader for all staffs. The use of MLT language in this organization tend to direction giving language, followed by empathetic language and meaning making language. The study suggest of develop MLT competence for leader especially in meaning making language to increase the organization vision of escalating the reading habit in Indonesia.